SOSIALISASI KEPADA PERANGKAT DESA: STRATEGI AWAL MEMBANGUN KERANGKA PARTISIPASI MASYARAKAT UNTUK WISATA RESILIEN DI DESA SUGIHEN TANAH KARO - Furqan, Furqan; Harefa, Mega Hernawati; Saridi, Sarmoko; Nasution, Rahmad Kurnia Abdik; Sinaga, Tuan Bobby Harsono (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2025)
This community service program aimed to strengthen the institutional capacity of the Sugihen Village apparatus in Juhar District, Karo Regency, by developing a participatory framework for resilient tourism. The program applied a participatory capacity building approach using the Participatory Learning and Action (PLA) method, which involved all village officials in socialization, group discussions, and the formulation of an initial action plan. Through workshops and interactive sessions, participants gained a deeper understanding of Community-Based Tourism (CBT) and the importance of collaborative and sustainable governance in tourism development. The results indicate an increased awareness and understanding among village officials regarding their strategic role as local leaders in tourism resilience. Furthermore, the activity successfully built institutional commitment and produced a preliminary participatory framework to guide broader community involvement. Nonetheless, certain limitations were identified, particularly in technical skills such as digital marketing and destination management, requiring follow-up training and mentoring. Overall, this program demonstrates that the success of resilient tourism development must begin with the empowerment of local actors through continuous and collaborative social learning. Sugihen Village holds strong potential to become a best practice model for community-based tourism development in the Karo region.